Expansion of Moso bamboo into Chinese fir stands persistently depletes rhizosphere bioavailable P pools: a seasonal, space-for-time approach - Bi, Shuangbo; Shi, Xuerong; Peng, Chunju; Hu, Tianyi; Chen, Jing; Xie, Jingchen; Li, Haicheng; Cao, Tingting; Shi, Man; Wang, Zhikang; Li, Quan; Song, Xinzhang (Frontiers in Plant Science, 2026)
IntroductionAccurate understanding of soil phosphorus (P) fractions is crucial for enhancing plant productivity and deciphering forest succession patterns; however, the dynamics of rhizosphere soil P fractions and their influencing factors during forest succession or land-type conversion, particularly in highly weathered tropical and subtropical regions, have not been comprehensively elucidated.MethodsUsing a space-for-time replacement strategy, in this study, we examined how Moso bamboo (Phyllostachys edulis) expansion into Chinese fir (Cunninghamia lanceolata) forests affects P fractions in rhizosphere soil across various seasons within a subtropical region. The research focused on seasonal variations in soil P dynamics resulting from this invasive expansion. We further evaluated key drivers, encompassing soil physicochemical characteristics and microbial traits.Results and discussionCompared to pure Chinese fir forests, mixed bamboo–fir stands had significant reductions in total P (excluding spring), CaCl2-P, Citrate-P, Enzyme-P (excluding spring), and HCl-P (excluding winter) throughout the seasonal cycle (p < 0.05). Pure bamboo forests showed further reduction in total P, Citrate-P, Enzyme-P, and HCl-P, along with reduced CaCl2-P (except summer and winter) (p < 0.05), with most P fractions (except CaCl2-P in summer, Citrate-P and HCl-P in summer and autumn, and Enzyme-P in summer) being lower in these stands than in mixed forests, which showed a decreasing trend with increasing expansion intensity. CaCl2-P, citrate-P, and HCl-P levels were consistently higher in summer and autumn than in winter and spring across Moso bamboo, Chinese fir, and mixed forest stands. Variations in P fractions were under the major control of nitrogen components and soil pH. This study highlights the importance of clarifying P fraction dynamics to understand forest succession mechanisms and informing P management strategies for enhancing forest productivity.